Too Much of a Good Thing? Using Tax Incentives to Stimulate Dual-Earner Couples - Henk-Wim de Boer; Egbert L. W. Jongen; Patrick Koot (Institute of Labor Economics (IZA), 2023)
Following major tax-benet reforms over the past decades, the Netherlands is the international front-runner in stimulating dual-earner couples via the tax system. In this paper we consider whether or not it has perhaps gone too far, using the inverse-optimal method of optimal taxation to recover the implicit social welfare weights for single- and dual-earner couples over time. Our results indicate that the reforms may have gone too far, leading to social welfare weights that are no longer monotonically declining in household income and even negative for some groups (suggesting Pareto-improving reforms are possible). We also consider optimal tax systems for dierent social preferences.
Keywords: C63; H21; H31; 330; optimal taxation; revealed social preferences; dual earners